Strategi Penataan Objek Wisata Danau Mas Harun Bastari di Kabupaten Rejang Lebong - Lili Imelda; Retno Agustina Ekaputri (Ecoplan, 2023)
The research aims to analyze the strengths, weaknesses, opportunities, and threats and determine the strategy for structuring the Lake Mas Harun Bastari Tourism object. This type of qualitative descriptive research. Descriptive data analysis method to support the analysis delivered through the SWOT analysis method. The study results from show that tourism in Lake Mas Harun Bastari Rejang Lebong is in quadrant three, indicating that tourism has high opportunities but weaknesses. Prioritizing the direction of development towards tourism management, the regional government is expected to be able to allocate the budget for developing tourism potential optimally and make tourism objects have their attractive so that they can compete with similar tourist objects in other regions. Trained and educated managing human resources will be able to manage tourist objects so that they have their charm. Tourism promotion and information systems are needed through advertisements, brochures, leaflets, or internet media to increase tourists.